Social Loafing pada Anggota Unit Kegiatan Mahasiswa Universitas Negeri Padang Menggunakan Pendekatan Thematic Analysis - Andira, Thasya Putri; Kurniawan, Rizal (YASIN, 2024)
Student Activity Unit (UKM) is the main forum for student self-development. However, UKM at Padang State University face several challenges related to the lack of member contributions to UKM work programs, especially after the COVID-19 pandemic and the emergence of the MBKM program. This study aims to understand the phenomenon of social loafing in UKM members at Padang State University by focusing on the reasons for joining, member contributions, barriers, and their impact on UKM. The study used qualitative methods with a thematic analysis approach through an open questionnaire on 200 active UNP students who became members of UKM in 2020-2022. The findings showed that respondents joined UKM because they wanted to develop themselves, improve social relations, match with interests and talents, increase experience, suitability of UKM with college majors, a good organizational environment, recommendations from others, fill spare time, and attractive attributes of UKM. Although many actively contribute, some members are less active due to factors such as perceived co-worker loafing, cohesivity, communication, and workload distribution at the organizational level. Individual factors such as time management, motivation, personal problems, adversity quotient, involvement in other activities, self-efficacy, passion, and academic stress also influence participation. These barriers can reduce the effectiveness of UKM with impacts such as unattainable targets, low participation, and high turnover. Impact on individuals such as physical and psychological disorders, decreased motivation, and suboptimal performance.